What About the Five-Membered Ring? Cyclopenta-fused Polycyclic Aromatic Hydrocarbons as a Building Block for Functional Materials - Plunkett, Kyle N. (Synlett, 2013)
There has been recent interest in creating new functional materials based on cyclopenta-fused polycyclic aromatic hydrocarbons (CP-PAH) that can be integrated into organic electronic devices. These five-membered-ring-containing materials are appealing because the electronic properties that are associated with their nonalternate PAH ring structure are not typically accessible by alternate PAH composed solely of six-membered rings. This paper highlights some recent synthetic advances for new CP-PAH systems and describes work from our lab that we believe has helped advance the methodology to create new CP-PAH-containing small molecules and polymeric materials.
Keywords: cyclopenta-fused polycyclic aromatic hydrocarbons; cross-coupling; electron acceptors; donor–acceptor copolymer; organic electronic materials